Potential risk from and prevention of phytoplankton outbreaks in blocking the cooling water system in a nuclear power plant on the Southeast China coast - Wang, Yu; Chen, Xiaoyin; Lin, Yingyue; Zhang, Shuyi; Chang, Lin; Tang, Xiaoming; Xiang, Peng; Lin, Heshan (Frontiers in Marine Science, 2022)
The invasion or aggregation of marine biota in coastal waters has become a common problem, threatening the safety of cooling water systems in the context of environmental and climate changes. However, studies on issues of coastal nuclear power plants from the view of marine ecology have mostly focused on the thermal effluent, entrainment effect on organisms, residual chlorine, radioactivity, etc. There is a lack of information on the safety of cooling water systems in nuclear power plants blocked by marine biota. Based on field and historical datasets, this study screened phytoplankton species that may potentially block the cooling water system of the Fuqing nuclear power plant on the Southeast China coast, identified the phytoplankton risk and a risk calendar, and established a catalog of risk phytoplankton species for the cooling water system. The screening criteria were simultaneously required as follows: (1) particle size of cells or group >2000 μm; (2) phytoplankton bloom or aggregation events occurred in surrounding areas; (3) and species abundance maintained at >0.5×105 cells/L in the surrounding area. Nine high-risk species were screened out that can easily form colonies, clusters, and groups, including Thalassiosira diporocyclus, Thalassiosira subtilis, Noctiluca scintillans, Phaeocystis globosa, Pseudo-nitzschia pungens, Pseudo-nitzschia delicatissima, Skeletonema costatum, Skeletonema dohrnii, Paralia sulcata. Due to small cells or the formation of short chains, some dominant phytoplankton species, even those with advantages in abundance and occurrence, had difficulty threatening the reliability of cooling water systems in nuclear power plants. The outbreak of different phytoplankton species varied daily, and the risk of blockage was highest from April to July. The biological characteristics, ecological mechanisms underlying outbreaks of high-risk phytoplankton species are reviewed and discussed, suggesting a high degree of temporal and spatial variability of blockage risk. Finally, main prevention and control measures used against high-risk phytoplankton species are provided to imply new ideas and methods for nuclear power plants. These strategies have very important practical and scientific significance.